1991
DOI: 10.1111/j.1699-0463.1991.tb05184.x
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody response to the major adhesin of Mycoplasma pneumoniae: Increase in titers against synthetic peptides in patients with pneumonia

Abstract: Hirschberg, L., Holme, T. & A. Krook. Human antibody response to the major adhesin of Mycoplasma pneumoniae: Increase in titers against synthetic peptides in patients with pneumonia. APMIS 99: 5 15-520, 199 1.Peptides corresponding to parts of the P1 protein (major adhesin) of Mycoplasma pneumoniae were synthesized. On the basis of predicted antigenicity, seven sequences containing 17 to 21 amino acids were selected. In addition, one peptide containing a sequence of 13 amino acids shown to be related to cytadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…EIAs are more sensitive for detecting acute infection than culture and can be comparable in sensitivity to PCR, provided that a sufficient time has elapsed since infection for antibody to develop and that the patient has a functional immune system. Crude multiantigen preparations, purified proteins (including the P1 adhesin), -capture approaches, purified glycolipids, and synthetic peptides have all been used as targets (22,64,116,190,191,203,303,399,425,445). Patient sera are incubated with the solid-phase antigen, and bound antibodies are visualized by using substrate and enzyme-labeled conjugates directed against the primary antibody.…”
Section: Serologymentioning
confidence: 99%
“…EIAs are more sensitive for detecting acute infection than culture and can be comparable in sensitivity to PCR, provided that a sufficient time has elapsed since infection for antibody to develop and that the patient has a functional immune system. Crude multiantigen preparations, purified proteins (including the P1 adhesin), -capture approaches, purified glycolipids, and synthetic peptides have all been used as targets (22,64,116,190,191,203,303,399,425,445). Patient sera are incubated with the solid-phase antigen, and bound antibodies are visualized by using substrate and enzyme-labeled conjugates directed against the primary antibody.…”
Section: Serologymentioning
confidence: 99%
“…P1 cytadhesin is one of the major antigens of M. pneumoniae that induce antibody production. Indeed, the anti-P1 antibody is frequently detected in the sera of M. pneumoniae pneumonia patients ( Hirschberg et al, 1991 ; Razin and Jacobs, 1992 ; Rastawicki et al, 1996 ; Tuuminen et al, 2001 ). Since the P1 protein exhibits amino acid sequence polymorphism between the type 1 and 2 lineages, there was a possibility that P1 proteins of types 1 and 2 have different immunogenicity and induce specific antibodies during infection.…”
Section: Serological Characterization Of M Pneumoniae mentioning
confidence: 99%
“…It has been reported that M. pneumoniae pneumonia patient sera exhibit inhibitory activity toward the adsorption of red blood cells to M. pneumoniae colonies [i.e., hemadsorption (HA) inhibitory activity; Hirschberg et al, 1991 ; Razin and Jacobs, 1992 ; Rastawicki et al, 1996 ; Tuuminen et al, 2001 ; Schurwanz et al, 2009 ]. Thus, we examined the HA inhibitory activity of the patient sera analyzed by western blotting in Figure 5B , and the results are shown in Table 2 .…”
Section: Hemadsorption (Ha) Inhibitory Activity Of M Pneummentioning
confidence: 99%
“…M. pneumoniae is difficult to culture and is not normally detectable in bronchial secretions (4); thus, serology is the principal method of laboratory diagnosis. M. pneumoniae has both lipid (7) and protein (5) antigens which elicit antibody responses in clinical infections. During the 1960s and 1970s, clinical laboratories used complement-fixing (CF) antibodies to M. pneumoniae or the presence of cold agglutinins to aid in diagnosing this infection (6).…”
mentioning
confidence: 99%